Porewater exchange drives the dissolved silicate export across the wetland‐estuarine continuum - Wang, Fenfang; Lu, Zeyang; Wang, Yao; Yan, Ruifeng; Chen, Nengwang (Frontiers in Marine Science, 2023)
Coastal wetland is an important hotspot for nutrient cycling and transport from the land to the ocean. Silicon (Si) as a vital biogenic element affects plant growth and health of coastal ecosystems. The understanding of key factors and processes controlling dissolved silicate (DSi) exchange between the wetland and coastal water has been limited due to the lack of measured data. We carried out intensive investigations of time-series DSi concentrations and porewater exchange across the Sediment-Water Interface (SWI) along a tidal creek with a mangrove-salt marsh gradient during neap and spring tides in 2020. Seasonal observations of surface water in a tidal creek and Zhangjiang Estuary (Fujian, China) were conducted from 2017 to 2020. The results showed that there was a net export of DSi from the mangroves to tidal creek with rates of 2.11 and 2.40 mmol m-2 d-1 in neap and spring tides, suggesting the mangroves served as the source of DSi. However, the salt marshes had a net DSi import with one or two orders of magnitude lower than the export from the mangroves. DSi export across the wetland‐estuary continuum was largely controlled by porewater exchange, groundwater geochemistry (pH, temperature) and plant root uptake. Groundwater in the mangroves has larger ratios of DSi:DIN (dissolved inorganic nitrogen) (2.5±0.6) and DSi:DRP (dissolved reactive phosphorus) (1257±35) compared with surface water. The net export of DSi from mangroves would modify the nutrient stoichiometry and mitigate the effects of reduced river DSi flux caused by damming on coastal ecosystem. This study provides new insights into the wetland Si cycling for sustaining coastal ecosystem health.